Reconceptualizing Justice: Utilizing The Fair Trial Principle As A Standard For A States’ Criminal Justice Systems - Prawira, M. Rizki Yudha (Ius Comparatum: Journal of Law Studies, 2025)
This publication emphasizes the critical importance of the right to a fair trial within the criminal justice system, highlighting its role in protecting human rights and ensuring justice. Referencing international treaties like the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR), the article illustrates that fair trials are a fundamental entitlement, requiring independent and impartial hearings. The principle serves as a safeguard against state abuses, such as arbitrary detention and torture, and encompasses essential guarantees like the presumption of innocence, the right to legal defense, and public hearings. These components are vital for preventing miscarriages of justice and maintaining transparency and accountability in the judicial process. Engaging with theories of justice, the article discusses John Rawls’ concept of fairness, which advocates for equitable treatment in the legal system. Amartya Sen emphasizes addressing real injustices, while Ronald Dworkin argues that individual rights, including the right to a fair trial, should not be compromised for the majority. Thus, the fair trial principle is foundational to the legitimacy of any criminal justice system.